Pearson New International Edition : Multivariate Data Analysis - Joseph F. Hair, William C. Black (Person Education Limited, 2014)
In this seventh revision, the organization of the chapters has been greatly simplified. New chapters have been added on structural equations modeling, and all sections have been updated to reflect advances in technology, capability, and mathematical techniques.